Titanium proximal femoral nailing for inter-trochanteric fractures of femur - Kumar Jose, Ashish; Kumar R, Surendher (International Journal of Medical Research and Review, 2015)
Introduction: Inter-trochanteric fractures of femur are one of the commonest fractures encountered in orthopaedic practice. It is mostly seen in the older age groups. An increased incidence of these fractures is noted these days owing to the increased life expectancy. Several implants have been designed for the treatment of these fractures. In this study we analyze the functional and radiological outcome of inter-trochanteric fractures fixed with titanium proximal femoral nail. Methods: This is a prospective study. 23 patients with inter-trochanteric fractures treated by titanium proximal femoral nail from August 2012 to December 2014 were included in the study. We analyzed these 23 patients for functional and radiological out come and complications. Results: The fracture union rate was 100 % and the average union time was 12 weeks. Varus mal-union was noted in 3 patients and shortening was seen in 1 patient. We did not encounter any infection in our study. 15 patients had excellent outcome, 7 had good outcome and 1 patient had fair outcome in our study (based on Kyle’s criteria). Conclusion: The result of our study shows that titanium proximal femoral nail is an excellent implant for the fixation of inter-trochanteric fractures of femur with very good functional and radiological outcome.